Implementation of the STAD Type Cooperative Learning Model in Islamic Education Learning in Integrated Islamic Elementary Schools - Pernandes, Rapi; Wirdati, Wirdati (Universitas Muhammadiyah Mataram, 2026)
Learning Islamic Religious Education (PAI) in Integrated Islamic Elementary Schools (SDIT) requires an approach that emphasizes not only mastery of knowledge but also the internalization of moral values and the formation of Islamic character in students. However, PAI learning practices still tend to be teacher-centered, resulting in low student learning activities. This study aims to describe the implementation of the Student Teams Achievement Division (STAD) cooperative learning model in PAI learning and analyze its contribution to improving student learning activities in SDIT. This study uses a qualitative approach with a descriptive design. Data were collected through observation, interviews, questionnaires, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that the implementation of STAD was well implemented and was able to improve student learning activities, especially in aspects of discussion participation, group work, courage to express opinions, and involvement in completing assignments. In addition, the implementation of STAD contributed to the internalization of moral values through structured social interactions. The novelty of this study lies in the contextualization of the STAD model as a value- based PAI learning approach in the SDIT environment. This study recommends the STAD model as an effective and relevant alternative for Islamic Education learning to improve the quality of the learning process in Islamic elementary schools.